Histopathologic Features of the Lung Cancer - Onder, Semen; Ozercan, Ibrahim Hanifi (Bentham Science Publ, 2013)
Lung cancer is one of the leading cause of cancer death in the world today. The predominant cause of the lung cancer is tobacco smoking. The other main causative agents are asbestos, silica, radon and heavy metals. Histologically carcinomas comprise nearly 99% of lung cancers. Lung carcinomas have two major groups in the classification of the World Health Organization [WHO]. There is a new multidisciplinary classification of lung adenocarcinomas published by the International Association for the Study of Lung Cancer, American Thoracic Society and European Respiratory Society. With the improvements in the knowledge of the lung cancer biology, there may be more changes in the histological classification and the treatment.
Keywords: Lung cancer; histology; classification; adenocarcinoma